2017
DOI: 10.1007/s11252-017-0673-2
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between socio-economic factors and biodiversity in urban ponds? A study in the city of Stockholm

Abstract: Urban small water bodies, such as ponds, are essential elements of human socio-economic landscapes. Ponds also provide important habitats for species that would otherwise not survive in the urban environment. Knowledge on the biodiversity of urban ponds and the relationship between their ecological value and factors linked to urbanization and socio-economic status is crucial for decisions on where and how to establish and manage ponds in cities to deliver maximum biodiversity benefits. Our study investigates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 53 publications
1
15
1
Order By: Relevance
“…This suggests that different taxonomic groups respond differently to the main urban drivers of biodiversity, as observed in a study of the species richness of different insect classes in ponds in Stockholm (Blicharska et al. ). Similarly, at the species level, responses to a set of environmental variables can be species‐specific, such that two species can respond in opposite ways to the same factor, as shown for aquatic plants (Ehrenfeld ) and amphibians (Hamer and Parris ).…”
Section: Biodiversity In Urban Pondsmentioning
confidence: 80%
See 1 more Smart Citation
“…This suggests that different taxonomic groups respond differently to the main urban drivers of biodiversity, as observed in a study of the species richness of different insect classes in ponds in Stockholm (Blicharska et al. ). Similarly, at the species level, responses to a set of environmental variables can be species‐specific, such that two species can respond in opposite ways to the same factor, as shown for aquatic plants (Ehrenfeld ) and amphibians (Hamer and Parris ).…”
Section: Biodiversity In Urban Pondsmentioning
confidence: 80%
“…Macroinvertebrate taxa tolerant of environmental pressures can also dominate in urban ponds, and this is the case with Oligochaeta or Chironomidae, which are often very numerous in terms of both abundance and species richness (Bishop et al 2000, Wood et al 2001, Lunde and Resh 2012, Mackintosh et al 2015, Hill et al 2017. This suggests that different taxonomic groups respond differently to the main urban drivers of biodiversity, as observed in a study of the species richness of different insect classes in ponds in Stockholm (Blicharska et al 2017). Similarly, at the species level, responses to a set of environmental variables can be species-specific, such that two species can respond in opposite ways to the same factor, as shown for aquatic plants (Ehrenfeld 2008) and amphibians (Hamer and Parris 2011).…”
Section: Species Richness In Urban Ponds Compared With Non-urban Pondsmentioning
confidence: 84%
“…Many use a diversity, or richness [3][4][5][6][7][8][17][18][19][20]23,26], whether measured at a single square metre [30] or whole city blocks. Other measurements of diversity that require abundance data, such as community composition, diversity indices, density or evenness are less frequently used [17,20,31]. A few studies of focal taxa, such as bats or other urban mammals, where a diversity is less informative, tend to focus on the abundance or occupancy of individual species to rsbl.royalsocietypublishing.org Biol.…”
Section: Measuring the Luxury Effectmentioning
confidence: 99%
“…Previous studies have explored how socioeconomics shapes plant diversity patterns, especially those indicated by species richness (Blicharska et al, 2017;Leong et al, 2018;McGill et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have explored how socioeconomics shapes plant diversity patterns, especially those indicated by species richness (Blicharska et al, 2017; Leong et al, 2018; McGill et al, 2015). Many of these studies have shown that the species richness of cities/urbanized areas is generally more influenced by human‐related or socioeconomic factors, such as economic level (i.e., GDP), urban greening percentage (or forest coverage), and human population density than environmental factors (Aronson et al, 2014; Avolio et al, 2015; Liu et al, 2017; Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%